2019
DOI: 10.1007/s10668-019-00357-w
|View full text |Cite
|
Sign up to set email alerts
|

Regional spatial patterns and influencing factors of environmental auditing for sustainable development: summaries and illuminations from international experiences

Abstract: Environmental auditing (EA) is an efficient tool for supervising environmental governance for the realization of economic and social sustainable development. However, the extent to which EA influences the implementation of environmental protection projects and the dominating socioeconomic factors affecting the implementation of EA are unclear. Due to limited data availability, reports investigating this issue are relatively scarce. Based on annual investigation data from the International Organisation of Supre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Jansons and Rivza (2017) find similarities amongst the Baltic SAIs. Also, proximity in characteristics amongst Western-Mediterranean countries has been already detected by Gonz alez-D ıaz et al ( 2008), Lu et al (2019) and Reichborn-Kjennerud et al (2019). They also confirm both DiMaggio's and Powell's normative and mimetic isomorphism, given all researched institutions are based on the same regulatory professional framework, either the ISSAIs or adapted ISSAIs, and the MS SAIs all converge towards ECA (Figures 1 and 2).…”
Section: Sais Similarity (Mds Model)supporting
confidence: 76%
See 1 more Smart Citation
“…Jansons and Rivza (2017) find similarities amongst the Baltic SAIs. Also, proximity in characteristics amongst Western-Mediterranean countries has been already detected by Gonz alez-D ıaz et al ( 2008), Lu et al (2019) and Reichborn-Kjennerud et al (2019). They also confirm both DiMaggio's and Powell's normative and mimetic isomorphism, given all researched institutions are based on the same regulatory professional framework, either the ISSAIs or adapted ISSAIs, and the MS SAIs all converge towards ECA (Figures 1 and 2).…”
Section: Sais Similarity (Mds Model)supporting
confidence: 76%
“…Also, proximity in characteristics amongst Western-Mediterranean countries has been already detected by González-Díaz et al. (2008), Lu et al. (2019) and Reichborn-Kjennerud et al.…”
Section: Resultsmentioning
confidence: 87%
“…Studies on the play of a government audit function are combined with the normative and empirical paradigm, and mainly focus on economic development, government governance, state-owned enterprise (SOE) governance, and so on. On the relationship between government audits and economic development, studies mainly focus on the impact of government audits on the transformation of the economic development mode and economic security, and most of them found that government audits can promote longterm economic development [22][23][24]. Studies about government audits and government governance have found that government audits can enhance government transparency, consolidate the operating efficiency of financial funds, improve government's disclosure of financial information [25][26][27][28], ensure financial security [29,30], and discourage or prevent the corruption of officials [31][32][33][34].…”
Section: The Function Of Government Auditingmentioning
confidence: 99%
“…At present, discussing the dynamic change process of land use from the perspective of coupling between human activities and the natural environment, and the dynamic change law of land use (Solomon et al, 2020) as well as its impact on the environment and ecology (Meer and Mishra, 2020;Msofe et al, 2020;Yang et al, 2022) from different levels is the focus of many scholars. However, it should be pointed out that, this kind of research results mainly came from the sociallly and economically developed areas (Guo et al, 2009;Lu et al, 2019), the ecologically environment fragile zones (Zhou et al, 2016;Zhao et al, 2018), and the urban fringe areas (Yang et al, 2011;Cui et al, 2013;Li et al, 2018). But there are relatively few studies on mountainous areas, especially from the perspectives of "mountain" and "basin" sub-regions, which have not attracted enough attention and formed a significant research system.…”
Section: Introductionmentioning
confidence: 99%